Changes in the Cardiac Index Induced by Unilateral Passive Leg Raising in Spontaneously Breathing Patients: A Novel Way to Assess Fluid Responsiveness - Zhao, Zhiyong; Zhang, Zhongwei; Lin, Qionghua; Shen, Lihua; Wang, Pengmei; Zhang, Shan; Xia, Zhili; Li, Fangfang; Xing, Qian; Zhu, Biao (Frontiers in Medicine, 2022)
Background: Evaluation of fluid responsiveness in intensive care unit (ICU) patients is crucial. This study was to determine whether changes in the cardiac index (CI) induced by a unilateral passive leg raising (PLR) test in spontaneously breathing patients can estimate fluid responsiveness. Methods: This was a prospective study, and 40 patients with spontaneous breathing activity who were considered for volume expansion (VE) were included. CI data were obtained in a semirecumbent position, during unilateral PLR, bilateral PLR, and immediately after VE. If the CI increased more than 15% in response to the expansion in volume, patients were defined as responders. Results：The results showed that a unilateral PLR-triggered CI increment of ≥7.5% forecasted a fluid-triggered CI increment of ≥15% with 77.3% sensitivity and 83.3% specificity with and an area under the receiver operating characteristic (ROC) curve of 0.82 [P<0.001]. Compared with that for bilateral PLR, the area under the ROC curve constructed for unilateral PLR-triggered changes in CI (ΔCI) was not significantly different (p=0.1544). Conclusions: ΔCI greater than 7.5% induced by unilateral PLR may be able to predict fluid responsiveness in spontaneously breathing patients and is not inferior to that induced by bilateral PLR.